(8x+7)(x-3)=0

Simple and best practice solution for (8x+7)(x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+7)(x-3)=0 equation:



(8x+7)(x-3)=0
We multiply parentheses ..
(+8x^2-24x+7x-21)=0
We get rid of parentheses
8x^2-24x+7x-21=0
We add all the numbers together, and all the variables
8x^2-17x-21=0
a = 8; b = -17; c = -21;
Δ = b2-4ac
Δ = -172-4·8·(-21)
Δ = 961
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{961}=31$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-17)-31}{2*8}=\frac{-14}{16} =-7/8 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-17)+31}{2*8}=\frac{48}{16} =3 $

See similar equations:

| -2-r/3=5 | | X+11=4x= | | 150-100+43650=45675-175m | | 5h=4=7h=24 | | 5t-22=33 | | 15x–7=8x+2 | | g(25)=24(-14-39) | | 3x+15=-32 | | -x8=96 | | 2i-16=12(i+8) | | t+19=20 | | 7x^2-242x+663=0 | | 12x-9=8x+2 | | 24=(x-39) | | 0.15+0.05(10-x)=0.10(10) | | 2-3s=-7.72 | | x=310 | | 3.7+2h=5.7 | | 3x-5(x-2)=-4+3-1 | | h/7-17=-11 | | -3v=-8-7v | | 30+0.50c=1.25c | | 7=-0.4+2.3x | | h/16=1 | | h4+10=14 | | −36=-12y=48 | | 4=f-14 | | +=117284d | | 2/3d+2=8 | | 2.7x-16.97=2.2 | | 12x+18=20x+78 | | 2k─(─20k)+16k─13k─5k=─20 |

Equations solver categories